PENERAPAN METODE DISKUSI DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS TONRONG KEC. RILAU ALE KAB. BULUKUMBA - Bahnur, Kurnia; Ramadhani, Selvi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
In the reality of implementing learning activities, teachers are accustomed to using conventional methods, where students are less actively involved in learning activities. Students tend to only hear and receive explanations from the teacher without being given the opportunity to express their opinions widely and openly. This study aims to find out about the application of the discussion method in improving student learning achievement in Akidah Akhlak subject at MTs Tonrong, kec. Rilau Ale, Kab. Bulukmba, knowing the advantages and disadvantages of applying the discussion method in improving student learning achievement at MTs Tonrong. The collection methods used in the study were observation, interview, and documentation using data analysis techniques in the form of data reduction and data presentation. The results of this study concluded that the application of the discussion method in learning akidah akhlak in improving achievement at MTs Tonrong is that the teacher takes 5 steps: 1.) Group division. 2) Each group discusses with group mates according to the predetermined theme. 3). The teacher assigns one of each group member to present the results of the discussion. 4) The discussion activity runs. 5). The teacher conveys conclusions and reinforcement of the material that has been discussed. The advantages and disadvantages contained in the discussion method at MTs Tonrong 1). Advantages, stimulating students to provide ideas or ideas, dare to express opinions. 2). Disadvantages, only a few students